A Note on Language, Law, and Society - Escobar, Alberto (1982)
This article examines the relationship between language, law, and society within the Peruvian context, with emphasis on the 1979 Constitution and its treatment of official languages and language policies. The author addresses the constitutional articles that regulate the official use of Spanish, Quechua and Aymara, and the policies on education and the cultural preservation of indigenous languages. In this regard, the social and political thought is discussed, including Manuel González Prada's theories on national identity and the lack of social cohesion in Peru. It also explores the history of multilingualism and the evolution of Peru's demographic and linguistic distribution, including internal mobility and urbanization, as factors that changed the social and linguistic configuration. Additionally, a comparison of the language policies of 1975 and 1979 is presented, critiquing the stereotypical educational approach and advocating for policies that address discrimination and inequality. Finally, the author reflects on Peru’s indigenist policy, emphasizing the importance of adopting a national rather than regional perspective, and the need to address social and economic problems in a comprehensive manner, advocating a more holistic approach that focuses on the social and economic roots of linguistic discrimination.